Effect of Protein Synthesis Modulator and Acute Heat Stress on Jejunal Morphology in Broiler Chicken - Jaiswal, S. K.; Tyagi, J. S.; Kolluri, G.; Gopi, M.; Dilliwar, L.; Chaturvedani, A. K. (International Journal of Bio-resource and Stress Management, 2016)
An experiment was conducted to assess the effect of protein synthesis modulator and heat stress on jejunal morphology in broiler chicken. A total one hundred ninety two of CARI-BRO Vishal broiler chicken were reared up to five weeks of age under standard managemental conditions and 36th day of age divided into three treatments including control, enhancer and inhibitor, receiving intra peritoneal normal saline, (0.5 ml) glutamine (0.75 mg kg-1 of BW) and quercetin (5 mg kg-1 of BW) respectively. After, 24 hours later each they were exposed to different duration of acute heat stress for 0, 2, 5 and 10 hours under 40±1 °C; 55% RH in psychometric chamber, after exposure of heat stress birds are immediately sacrificed (n-4 for each exposure duration) and jejunum tissue sample were collected in 10% formal saline and further processed for morphological study. A significant (*p<0.05) effect of protein synthesis modulator on jejunal morphological parameters was observed in broilers exposed to varied periods of heat stress. Protein synthesis modulator revealed a significant effect (*p<0.05) on villi length of jejunum however heat stress exposure and duration of heat stress did not show any significant effect (p>0.05) on jejunal morphological observations as compared to normal villi length, crypt depth and villi length to crypt depth ratio. It was concluded that protein synthesis modulator glutamine protect intestinal morphology under heat stress condition.